Dual efficacy of Fasudil at improvement of survival and reinnervation of flap through RhoA/ROCK/PI3K/Akt pathway. Issue 8 (22nd March 2022) - Wang, Hai; Fang, Fang; Chen, Shaofeng; Jing, Xing; Zhuang, Yuehong; Xie, Yun
Abstract: Fasudil is reported to be effective at protecting against ischaemic diseases, and at augmenting axon growth. In this study, we aim to evaluate its efficacy in promoting flap survival and reinnervation. Ninety‐two Institute of Cancer Research (ICR) mice were used and divided into the control, Fasudil, LY294002, Fasudil+LY294002 groups, receiving a daily intraperitoneal injection of normal saline, Fasudil (10 mg/kg), LY294002 (5 mg/kg), and Fasudil (10 mg/kg) + LY294002 (5 mg/kg), respectively. On days 0 and 5, the blood perfusion and diameter of the iliolumbar artery in the pedicle of the flaps in the four groups were evaluated using laser speckling contrast imaging (LSCI). On day 5, the flaps were photographed and the necrosis rate of the flaps was calculated using Photoshop CS6. In addition, tissues were harvested from the flaps and divided into two parts. One part underwent routine cryosection and immunofluorescent staining using the antibody against CD31 for evaluation of the microvascular density in the four groups. In the other part, the expression of RhoA, ROCK1+2, p‐CPI‐17, p‐MYPT, p‐PTEN, p‐PI3K, p‐Akt, and vascular endothelial growth factor (VEGF) within the flaps were determined using western blotting. Moreover, at days 0, 7, 15, and 30 after flap surgery, the axons within the flaps were evaluated using immunofluorescent staining with the antibody against Neurofilament‐200. It turned out that the necrosis rate was (24.4 ± 7.7)%, (5.2 ± 1.6)%, (29.8 ± 4.2)%, and (30.9 ± 7.1)%, respectively, in the control, Fasudil, LY294002, LY294002+Fasudil groups. There was a significant reduction in the necrosis rate of the flaps in the Fasudil group ( P  < .001). The LSCI and immunofluorescent staining demonstrated that Fasudil could significantly expand the diameter of the iliolumbar artery in the pedicle, boost the overall blood perfusion, and increase the microvascular density of the flaps in the Fasudil group ( P  < .05), which could all be abolished by PI3K inhibitor LY294002. On day 5, the expression of p‐CPI‐17, p‐MYPT, and p‐PTEN were downregulated, whereas pPI3K, p‐Akt, and VEGF were upregulated in the Fasudil group ( P  < .001). As for reinnervation, Neurofilament‐200 fluorescent staining revealed that at days 15 and 30 after flap harvest, only in the Fasudil group could new axons be observed. It can be concluded that Fasudil could simultaneously improve the survival and axon growth after flap harvest, a dual efficacy achieved by inhibition of the RhoA/ROCK pathway, which in turn activates /PI3K/AKT pathway.